PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) BERBANTUAN MEDIA SPIN WHEEL DALAM PEMBELAJARAN MENULIS TEKS PIDATO SISWA KELAS VIII SMP MUHAMMADIYAH 16 LUBUK PAKAM - Harahap, Elvi Maulida; Harahap, Rosmawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine: (1) the learning of speech text writing among eighth-grade students of SMP Muhammadiyah 16 Lubuk Pakam without the application of the Teams Games Tournament (TGT) cooperative learning model assisted by Spin Wheel media, (2) the learning of speech text writing with the application of the TGT cooperative learning model assisted by Spin Wheel media, and (3) the differences in students’ speech text writing outcomes between the control and experimental classes. This study employed an experimental method with a Posttest-Only Control Group Design. The population consisted of all eighth-grade students of SMP Muhammadiyah 16 Lubuk Pakam. The sample included two classes: class VIII-A as the control class and class VIII-B as the experimental class, each consisting of 21 students. Data were collected through speech text writing tests, observation sheets, and documentation. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing using the t-test. The results showed that speech text writing learning without the application of the TGT cooperative learning model assisted by Spin Wheel media was still conducted conventionally and teacher-centered, resulting in an average score of 69.57, categorized as fair. Meanwhile, the implementation of the TGT cooperative learning model assisted by Spin Wheel media was carried out according to the learning syntax, namely presentation, team study, tournament, and recognition. The application of the model made students more active, enthusiastic, and motivated, resulting in an average score of 82.47, categorized as good. The hypothesis test results showed that the significance value was less than 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, the application of the TGT cooperative learning model assisted by Spin Wheel media had a significant effect on students’ speech text writing skills.